2016
DOI: 10.3329/bjvm.v14i1.28827
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Coxiella Burnetii Infection in Cattle, Black Bengal Goats and Ticks in Bangladesh

Abstract: The objectives of this study were to determine the prevalence of Coxiella burnetii infection in domestic ruminants and to detect Coxiella burnetii DNA from ticks and serum samples. A total of 24 ticks, 91 goats and 81 cattle serum samples with the history of abortion and reproductive disorders were collected from the different areas in Bangladesh. The serum samples were tested by CHEKIT Q-Fever Antibody ELISA Test Kit and Coxiella burnetii DNA was detected by multiplex quantitative realtime PCR. The overall pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Animals may be shedding bacteria and/or remain seropositive long after the acute infection [ 39 , 40 ]. Other authors reported significantly higher seroprevalence in goats than in cattle [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animals may be shedding bacteria and/or remain seropositive long after the acute infection [ 39 , 40 ]. Other authors reported significantly higher seroprevalence in goats than in cattle [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A standard curve was generated using decimal dilutions of the positive control. The PCR primer sequences and conditions were applied as described by Chakrabartty et al 2016 [25].…”
Section: Methodsmentioning
confidence: 99%
“…According to a recent report by Chakarabarthy et al , the overall seroprevalence of coxiellosis in Bangladesh was 7.6% and 6.1% for goats and cattle, respectively. However, none of seropositive samples were positive for C. burnetii DNA in real-time PCR [ 35 ]. Two researchers observed that C. burnetii appears to be quite frequent in blood as well as milk products of cattle [ 14 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, none of seropositive samples were positive for C. burnetii DNA in real-time PCR [ 35 ]. Two researchers observed that C. burnetii appears to be quite frequent in blood as well as milk products of cattle [ 14 , 35 ]. Kim et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation